Conclusions and results of colonoscopy at Tishreen University Hospital during 2018 - zayzafon, Hasan; aentaneos, Melad; esa, mazen ghad (Latakia University Journal -Medical Sciences Series, 2019)
Introduction: Colonoscopy is now considered a routine procedure in gastrointestinal practice, and the current gold standard in diagnosis and evaluation of colonic pathologies. It is the most accurate diagnostic tool of colonic mucosal lesions when suspected clinically or radiologically. Aim: This study will allow to assess the diagnostic outcome of colonoscopy at Tishreen University Hospital in 2018, evaluating the diagnostic yield of colonoscopy and the correlation between indications and outcome of colonoscopy, as well for unplanned events and its percentage. Methods: This is a hospital‑based observational descriptive study that has been carried out in Tishreen University Hospital, Lattakia, Syria between January, 2018 and December, 2018. All patients were approached before colonoscopy, detailed examination and questioning were carried out, followed by the colonoscopy procedure. All endoscopic findings were recorded, as well as endoscopic unplanned events, and total procedure time. Results: A total of 601 patients went colonoscopy (323 males, 278 females), the median age was 55 years with a range of 83 years. The indications for colonoscopy were abdominal pain (33.8%), iron deficiency anemia (26.3%), lower-gastrointestinal bleeding (22.8%), constipation (17.8%), diarrhea (16.3%), weight loss (12.1%), screening (4.3%), and other indication of 16.8% that included search for a primary tumor (4.5%), obstipation (3.7%), and assessment of parametrial invasion of the rectum in cervical cancer (1.5%) Despite the at least 10 major pathologies seen on colonoscopy, normal cases constituted the majority (36.3%). The most common endoscopic findings were hemorrhoids (24.1%), polyps (16.5%), inflammatory bowel disease IBD (11.3%), colorectal cancer CRC (10.3%); 85.5% of CRC were located in the left side of the colon. Diverticulosis were found in 5.5%, infectious colitis in 2.5%, and angiodysplasia in 1.8%. The diagnostic yield was 63.7%. Pain was the most encountered unplanned event that has been seen in 90% of cases, mostly of mild intensity. Serious complications were encountered in 5 cases (0.83%), consisted of 3 post polypectomy bleeding (0.5%), 1 respiratory arrest (0.16%), and 1 perforation (0.16%); none of them ended in patients’ permanent harm or death. Total procedure time (TPT) for colonoscopy was 24.2 ± 12.3 minutes. Conclusion: In Syrian patients went colonoscopy at Tishreen University Hospital, Lattakia during 2018, the most prevalent indication was abdominal pain followed by anemia and lower GI bleeding. The most common finding was hemorrhoids, followed by benign polyps and IBD. CRC was found in 10.3% of cases. We detected a significant correlation between patients’ chief complaint and colonoscopic findings with regards to CRC and IBD. In general, colonoscopy was safe and few serious complications were recorded. المقدمة: يعدّ الآن تنظير الكولونات من الإجراءات الروتينية بالحقل الهضمي، ووسيلة الاستقصاء الذهبية لتشخيص ودراسة الموجودات المرضية في الكولون، وهو الوسيلة الأكثر دقة في تشخيص آفات مخاطية الكولون عند الشك بها سريريا أو شعاعيا. الهدف: ستسمح هذه الدراسة بمعرفة النتاج التشخيصي وطيف الإمراضيات الكولونية المنتشرة في منطقتنا الجغرافية متمثلة بمراجعي مشفى تشرين الجامعي خلال عام 2018، إضافة لدراسة العلاقة الترابطية بين استطباب تنظير الكولون والموجودات التنظيرية المرضية. كما ستسمح بدراسة الاختلاطات الحاصلة أثناء التنظير. المواد والطرائق: هذه الدراسة دراسة رصدية وصفية أجريت في مشفى تشرين الجامعي في اللاذقية بين كانون الثاني وحتى كانون الأول من عام 2018. تم مقاربة جميع المرضى قبيل البدء بالتنظير، أجري الفحص والاستجواب المفصّل عن الأعراض التي استطبت إجراء تنظير الكولون لهم، وسجلت الموجودات التنظيرية المرضية أو الطبيعية، كما سجلت الاختلاطات الحاصلة أثناء التنظير، بالإضافة لزمن التنظير الكامل. النتائج: اشتملت الدراسة على 601 مريضا (323 ذكرا، و278 أنثى) أجري لهم تنظير الكولون، بواســـط أعمــار 55 ســــنة مع مــدى 83 ســــنة. كــانت اســتطبابات تنظيـر الكـــــولـون هــــي الألــم البطنــــي (33.8%)، فقر الدم العوزي (26.3%)، النزف السفلي (22.8%)، الإمساك (17.8%)، الإسهال (16.3%)، نقص الوزن (12.1%)، والمسح الاستقصائي في 4.3%. كما كانت 16.8% من الحالات تابعة لاستطبابات أخرى أهمها البحث عن مصدر ورمي بدئي (4.5%)، انسداد الأمعاء (3.7%)، وتقييم ارتشاح ورمي إلى المستقيم من ورم عنق الرحم (1.5%). كان نتاج التنظير طبيعياً في 36.3%. أهم الموجودات التنظيرية المرضية كانت البواسير (24.1%)، البوليبات (16.5%)، الداء المعوي الالتهابي (11.3%)، سرطان الكولون والمستقيم (10.3%) كان منها 85.5% بالجهة اليسرى للكولون. وشوهد داء الرتوج (5.5%)، التهاب الكولون الانتاني (2.5%) والتشوهات الوعائية (1.8%). وكان النتاج التشخيصي diagnostic yield 63.7%. كان الألم هو أكثر الاختلاطات مشاهدة بنسبة 90% معظمه من الدرجة الخفيفة. أما الاختلاطات الهامة فشوهدت في 0.83% فقط وكانت عبارة عن 3 حالات نزف تالٍ لاستئصال بوليبات (0.5%)، وحالة تثبيط تنفسي واحدة (0.16%) وحالة انثقاب واحدة (0.16%)؛ لم يسفر أي من هذه الاختلاطات عن أذية دائمة أو وفاة للمريض. زمن التنظير الإجمالي 24.2±12.3 دقيقة. الخلاصة: لدى المرضى الذين أجري لهم تنظير الكولون في مشفى تشرين الجامعي كان الألم لبطني هو العرض الأكثر مشاهدة، متبوعا بفقر الدم العوزي والنزف السفلي. كانت البواسير هي أكثر الموجودات التنظيرية، تلتها البوليبات والداء المعوي الالتهابي. شوهدت أورام الكولون والمستقيم في 10.3% من التناظير، مع سيطرة لأن تكون بالجهة اليسرى للكولون. كما وجدنا علاقة ترابطية بين الاستطباب التنظيري ونتاج التنظير فيما يخص الداء المعوي الالتهابي وأورام الكولون والمستقيم. ويعدّ تنظير الكولون بشكل عام إجراء آمن، مع نسبة منخفضة جدا من الاختلاطات الهامة. إجمالي زمن تنظير الكولون المتوقع 24.2±12.3 دقيقة.